2016
DOI: 10.1186/s12998-016-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

The new chiropractic

Abstract: BackgroundPhysical manipulation and manual therapies are thousands of years old. The most popular western world iteration of these therapies is delivered by chiropractors. It can be argued that the collective public health benefit from chiropractic for spinal pain has been very substantial, however as chiropractic has transitioned from craft to profession it has encountered many internally and externally driven machinations that have retarded its progress to a fully accepted allied health profession. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…In the quest to reform the profession, this may be the one of the more important principle to address. In fact, this encourages the answering of Vidal’s [32] question of “what is good and what is evil?” Furthermore, this principle addresses Walker’s [15] concern of individual personal leadership to effect change and Ausman’s [16] concern about the loss of ethics and morality.Principle of Custom, Convention, and ContinuityKirk [37, 38] determined three aspects of human life that were essential: custom, convention and continuity. These three aspects are necessary ingredients for the sustaining of societies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the quest to reform the profession, this may be the one of the more important principle to address. In fact, this encourages the answering of Vidal’s [32] question of “what is good and what is evil?” Furthermore, this principle addresses Walker’s [15] concern of individual personal leadership to effect change and Ausman’s [16] concern about the loss of ethics and morality.Principle of Custom, Convention, and ContinuityKirk [37, 38] determined three aspects of human life that were essential: custom, convention and continuity. These three aspects are necessary ingredients for the sustaining of societies.…”
Section: Discussionmentioning
confidence: 99%
“…spinal manipulation and the profession as chiropractic medicine with appreciation for the social contract . These three aspects of the Principle of Custom, Convention, and Continuity are applicable to Walker’s [15] suggestion for establishment of a progressive identity.Principle of PrescriptionKirk [37, 38] defined the Principle of Prescription as those things established by immemorial usage, so that the minds of humans do not run to the contrary. The spirit of this principle is that one’s greatness as a profession and nation comes from the hard work and inspiration of those who have come before [37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have recently lamented the continued chiropractic inclination to use outdated and anatomically incorrect language to describe the nature of the manipulable lesion (''subluxation'') and the method of treatment (''adjustment''). 2,3,11 This terminological idiosyncrasy has plagued the profession since its founding. It creates confusion in the minds of nonchiropractic health care providers and at the same time propagates the continuance of the simplistic and outdated (and some would say offensive) bone-out-of-place model, not only in the minds of health care consumers, but sadly also in the minds of naive or poorly educated chiropractic providers.…”
Section: From Esoteric To Evidencementioning
confidence: 99%
“…In a 2015 keynote speech delivered to the Chiropractic & Osteopathic College of Australasia, Bruce Walker, head of discipline for chiropractic and associate dean of research in the School of Health Professions at Murdoch University in Australia, gave as one of the keys to fully legitimize the profession that content be taught ''in the context of the evidence and that students obtain the necessary training to question and critically appraise.'' 22 We identified that a concerted and deliberate redesign at the level of the program was necessary to effect the systemic changes required to answer this need. We were also mindful to retain our alignment of course and unitlearning outcomes and assessment against the Australian Qualifications Framework specifications.…”
Section: Introductionmentioning
confidence: 99%